العنف والتسامح في اليهودية والإسلام - حريش حدة (University of Eloued جامعة الوادي, 2024)
انتشار ظاهرة العنف وتزايد حدتها يوما عن يوم لم يأت من فراغ، بل هو نتيجة عقائد وافكار تغذت من خطابات دينية ومظهر من مظاهر السيطرة على الآخر ،واستعباده فبقدر ما تحمله الخطابات الدينية من كراهية وحقد وعنصرية بقدر ما يغيب التسامح وتشتعل نيران العنف في العالم ،و في هذا المقال المتواضع نتناول موضوع العنف والتسامح في اليهودية والإسلام وتحديد نظرة كل من الديانتين للآخر. Abstract: The wide spread of the phenonmenon of violence. and the increasing of its intensity in the world doesn't come from nothingness, but, it is the result of different thoughts and ideologies nourished by relegious discourses and a manifestation of over control and enslaving of others . So, the more relegious discourses carry hate, hatred and racism , the more tolerance is absent and violence flames are broken out . In this report, we tackle the subject of violence and tolerance in Judaism and Islam and set how each relegion views the other one
Keywords: العنف; التسامح; الآخر; الخطاب الديني; اليهودية; الإسلام; Violence; Tolerance; other; the speech relegious; Judaism; Islam